Studi e ricerche di scienze umane e sociali Studies and Researches in Human and Social Sciences Authors - Roberto Delle Donne (Scuola delle Scienze Umane e Sociali. Quaderni, 2014)
This book belongs to a new Series promoted by the School of Humanities and Social Sciences at Federico II University of Naples, in order to facilitate dialogue among scholars from different disciplines and to encourage interdisciplinary and cross-sectoral approaches on topics, both contemporary and historical. The studies collected in this volume offer a graceful synthesis of past and present, as is typical of the humanities, that study human culture in all its form.